PENGARUH KINERJA LINGKUNGAN, STRUKTUR MODAL, DAN PERPUTARAN MODAL KERJA TERHADAP PROFITABILITAS PADA PERUSAHAAN SEKTOR PERTAMBANGAN - Kusuma Indawati Halim; Veronica Olivia; Novianty Novianty (LPPM Universitas Bina Bangsa, 2022)
Profitability is an important factor related to financial decision making. The higher the profitability of the company, the greater the level of investor confidence in the company. This study aims to determine the effect of environmental performance, capital structure, and working capital turnover on profitability in mining sector companies on the Indonesia Stock Exchange with the 2016-2020 research period. The population is 47 companies with a sample of 16 companies determined using the purposive sampling method. The data analysis technique used multiple linear regression analysis. Data processing uses SPSS version 26. The test results show that environmental performance has no effect on profitability, while capital structure and working capital turnover have a positive effect on profitability. The coefficient of determination shows that the independent variable in explaining the dependent variable is only 13.5 percent, while 86.5 percent is influenced by other factors which is not examined in this study